Analisis Sisa Masa Layan Perkerasan Lentur Berdasarkan Prediksi Kerusakan dengan Metode MEPDG dan Prediksi Nilai Kondisi Perkerasan - Cahyono, Muhammad Wardan B.; Suparma, Latif Budi; Mulyono, Agus Taufik (Diponegoro University, 2022)
The Remaining Service Life (RSL) of the pavement can be used to assist in determining the proper timing of maintenance work. This study aims to analyze the value of the remaining service life of flexible pavement based on the prediction of damage that occurs using the MEPDG method and based on the prediction of pavement performance conditions with the Pavement Condition Index (PCI) value. Three roads in D.I. Yogyakarta is used as the object of research, namely the Milir-Sentolo, Pakem-Prambanan, and North-West Arteries. Prediction of the remaining service life of the pavement is calculated based on the prediction of the amount of damage. The types of damage predicted were rutting, alligator cracking, and longitudinal cracking. The pavement response value is obtained from the results of the analysis using the Kenpave program with the modulus of elasticity of the material for each layer as input. The results of the analysis show that the Pakem-Prambanan road segment has the longest remaining service life, both based on the prediction of pavement damage (³ 14th year), and the predicted PCI value (7th year). This is because this section serves the least traffic compared to others